Priming of Mesenchymal Stem Cells for Enhanced Interleukin-10 Secretion via Conditioned Medium from Lipopolysaccharide-Activated Peripheral Blood Mononuclear Cells - Prasetio, Ardi; Syafitri, Luthfiana Mifta; Prabowo, Adam; Alif, Iffan; Nurichsan, Aldan (International Journal of Cell and Biomedical Science, 2023)
Background: Mesenchymal stem cells (MSCs) are known for their immunomodulatory properties, particularly their ability to secrete anti-inflammatory cytokines such as interleukin-10 (IL-10). Enhancing the secretion of IL-10 by MSCs could have significant therapeutic potential for treating inflammatory diseases. Objective: This study aimed to prime the secretion of IL-10 by MSCs through the use of conditioned medium (CM) derived from lipopolysaccharide (LPS)-induced peripheral blood mononuclear cells (PBMCs). Methods: MSCs were isolated from Wharton’s Jelly and characterized using flow cytometry and differentiation assays. PBMCs were isolated from human blood samples and stimulated with LPS to produce a pro-inflammatory environment. The conditioned medium from these LPS-induced PBMCs was collected and add to MSCs culture medium in 5% and 7.5%. After 24h and 48h incubation, IL-10 secretion by MSCs was measured using an enzyme-linked immunosorbent assay (ELISA). Results: The results demonstrated that MSCs cultured in the conditioned medium from LPS-induced PBMCs showed a significant increase in IL-10 secretion compared to control conditions in 24h exposure, but not significantly different in 48h. Conclusion: The exposure of conditioned medium from LPS-induced PBMCs may effectively enhances the secretion of IL-10 by MSCs.